2014
DOI: 10.1016/j.virol.2014.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of innate immune signaling by the secreted form of the West Nile virus NS1 glycoprotein

Abstract: West Nile virus (WNV) employs several different strategies to escape the innate immune response. We have previously demonstrated that the WNV NS1 protein interferes with signal transduction from Toll-like receptor 3 (TLR3). NS1 is a glycoprotein that can be found intracellularly or associated with the plasma membrane. In addition, NS1 is secreted to high levels during flavivirus infections. We investigated whether the secreted form of NS1 inhibits innate immune signaling pathways in uninfected cells. Secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…NS1 is believed to function as a co-factor in viral RNA replication [14], though reports regarding interaction of NS1 with TLR3 are contradictory [65]. Some studies have shown the increased presence of TLR3 in WNV infection in vivo [66]. Another study indicated that WNVNS1 inhibits TLR3 signal transduction [67,68], whereas the NS1 protein of several mosquito-borne flaviviruses cannot inhibit TLR3 signalling [69].…”
Section: The Innate Immune Response To Avian Tmuv Infectionmentioning
confidence: 99%
“…NS1 is believed to function as a co-factor in viral RNA replication [14], though reports regarding interaction of NS1 with TLR3 are contradictory [65]. Some studies have shown the increased presence of TLR3 in WNV infection in vivo [66]. Another study indicated that WNVNS1 inhibits TLR3 signal transduction [67,68], whereas the NS1 protein of several mosquito-borne flaviviruses cannot inhibit TLR3 signalling [69].…”
Section: The Innate Immune Response To Avian Tmuv Infectionmentioning
confidence: 99%
“…Similar to other known flaviviruses, DTMUV has an approximately 11 kb single-stranded positive-sense RNA genome, which contains a single ORF that encodes three structural proteins (C, prM, and E) and seven nonstructural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5), flanked by the 5¢ and 3¢ untranslated regions (UTRs). The structural proteins are supposed to be involved in cellular attachment, membrane fusion and virion assembly, and the nonstructural proteins are responsible for genome replication and counteraction of host immunity, in similar mechanisms to other known pathogenic flaviviruses (Avirutnan et al, 2010;Best et al, 2005;Crook et al, 2014;Jones et al, 2005;Munoz-Jordan et al, 2003;Werme et al, 2008). DTMUV is highly pathogenic for ducks, and exhibited neurotropic effects in a mouse model Tang et al, 2013).…”
mentioning
confidence: 99%
“…Produced as a single polyprotein, it is cleaved by both host and viral proteases to give rise to the individual proteins (Lindenbach & Rice, 2003). NS1 is a multifunctional glycoprotein involved in the formation of the replication complex (Chu & Westaway, 1992;Khromykh et al, 1999Khromykh et al, , 2000Lindenbach & Rice, 1997;Westaway et al, 1997;Youn et al, 2012) and the modulation of the host immune response (Avirutnan et al, 2006(Avirutnan et al, , 2010Chung et al, 2006;Crook et al, 2014;Kurosu et al, 2007;Muller & Young, 2013;Schlesinger, 2006;Wilson et al, 2008). After cleavage from the polyprotein (Falgout & Markoff, 1995;Nowak et al, 1989), NS1 is glycosylated and forms a heat-labile dimer in the endoplasmic reticulum (ER) (Pryor & Wright, 1994;Winkler et al, 1988Winkler et al, , 1989.…”
Section: Introductionmentioning
confidence: 99%